2016
DOI: 10.4236/ojms.2016.62021
|View full text |Cite
|
Sign up to set email alerts
|

The Time Series Spectral Analysis of Satellite Altimetry and Coastal Tide Gauges and Tide Modeling in the Coast of Caspian Sea

Abstract: This study endeavors to deal with the least square spectral analysis on the time series, to find present significant frequencies, to analyze 40 tide components using harmonic methods and to show relationship between discovered frequencies and 40 components of tide. For the purpose of collecting data of altimetry satellites of Topex/Poseidon (T/P), Jason 1, Jason 2 and coastal tide gauges of Bandar Anzali, Noshahr, and Nekah were utilized. In this time series formed by cross over points of altimetry satellite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…To address this issue, a waveform retracking method known as the adaptive leading edge sub-waveform (ALES) is applied to correct the range observations [16]. Additionally, inherent uncertainties exist in satellite altimetry measurements, including errors introduced by geophysical and environmental factors, which are typically addressed through global or local modeling techniques [23,24]. Moreover, the systematic errors, such as radial error [24], present in the satellite altimeter datasets require calibration, which is considered as described in [25].…”
Section: Data Descriptionmentioning
confidence: 99%
“…To address this issue, a waveform retracking method known as the adaptive leading edge sub-waveform (ALES) is applied to correct the range observations [16]. Additionally, inherent uncertainties exist in satellite altimetry measurements, including errors introduced by geophysical and environmental factors, which are typically addressed through global or local modeling techniques [23,24]. Moreover, the systematic errors, such as radial error [24], present in the satellite altimeter datasets require calibration, which is considered as described in [25].…”
Section: Data Descriptionmentioning
confidence: 99%
“…The range observation is contaminated by some source of errors which must be corrected via global or local modeling and can be summarized as follows: wet troposphere correction, dry troposphere correction, ionosphere correction, electromagnetic bias correction, ocean tide correction, inverse barometer correction, pole tide correction and center of gravity movement. They are better known as "geophysical corrections" [Benada, 1997;Pirooznia et al, 2016a;Soltanpour et al 2017]. Also the re-tracking correction is used to correct range observation.…”
Section: Re-tracking Of Sa Observationsmentioning
confidence: 99%
“…Pirooznia et al [7] used the least-squares spectral (LSS) analysis method to examine sea-level time series of altimetry data (TOPEX/Poseidon, Jason-1, and Jason-2) and three tide gauges located in the Caspian Sea. The spectral analysis revealed that solar annual (Sa) signals play a dominant role in sea-level variation of the Caspian Sea.…”
Section: Introductionmentioning
confidence: 99%